2014
DOI: 10.1007/s10551-014-2218-4
|View full text |Cite
|
Sign up to set email alerts
|

Why Sparing the Rod Does Not Spoil the Child: A Critique of the “Strict Father” Model in Transnational Governance

Abstract: The United Nations Global Compact (UNGC) is one of the largest transnational governance schemes (TGSs). Its success or failure, however, is a matter of debate. Drawing on research in cognitive linguistics, we argue that when evaluators discuss the UNGC, they apply the metaphorical concept of the family: the UNGC corresponds to the ''family,'' the UNGC headquarter to the ''parent'' and the business participants of the UNGC to the ''children'' of the family. As a corollary, evaluators' implicit understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 60 publications
1
18
0
1
Order By: Relevance
“…Studies by Pichler (2013) and Ponte and Cheyns (2013), for example, have shown how the RSPO’s certification rules favor larger estates that can achieve economies of scale, while small-scale farmers often have problems obtaining certification. Other authors focus on the implications of unspecific rules, especially in relation to principle-based MSIs (Haack & Scherer, 2014; Sethi & Schepers, 2014), and on how their alignment with Western values limits their uptake. Pattberg (2006) argues that the perception of what counts as “good forest management” is mostly based on Western scientific standards (see also Hatanaka, 2010; Ponte, 2012) and that this has implications for which kinds of actors can comply more easily with relevant MSIs.…”
Section: Main Themes Of Msi Researchmentioning
confidence: 99%
“…Studies by Pichler (2013) and Ponte and Cheyns (2013), for example, have shown how the RSPO’s certification rules favor larger estates that can achieve economies of scale, while small-scale farmers often have problems obtaining certification. Other authors focus on the implications of unspecific rules, especially in relation to principle-based MSIs (Haack & Scherer, 2014; Sethi & Schepers, 2014), and on how their alignment with Western values limits their uptake. Pattberg (2006) argues that the perception of what counts as “good forest management” is mostly based on Western scientific standards (see also Hatanaka, 2010; Ponte, 2012) and that this has implications for which kinds of actors can comply more easily with relevant MSIs.…”
Section: Main Themes Of Msi Researchmentioning
confidence: 99%
“…Accordingly, our study also supports research that aimed to counterbalance the 'organizing bias' for perceiving order as an imperative of success, which characterizes much of the research in organization studies, including extant works following the CCO perspective (as remarked by Bisel, 2009: 632). Our study shows that disordering is an integral part of efforts of ordering and thus can also be extended to explore the (dis)ordering properties of communication in the context of technical standardization (e.g., van den Ende et al, 2012) or CSR standardization processes (e.g., Haack and Scherer, 2014), for instance.…”
Section: Discussionmentioning
confidence: 86%
“…Van den Ende et al, 2012) or CSR standardization processes (e.g. Haack and Scherer, 2014), for instance.…”
Section: Discussionmentioning
confidence: 99%
“…O estabelecimento de um marco regulatório normativo e com força de tratado internacional iria contrariar a opção do representante especial para empresas e direitos humanos na ONU, John Ruggie (2004aRuggie ( , 2013. Outros autores também entendem que a aproximação entre empresas e direitos humanos deve estar calcada na construção de consensos (HAACK;SCHERER, 2014). Dessa maneira, busca-se uma alternativa de comprometimento paulatino, dentro do possível (RUGGIE, 2013).…”
Section: Amon Barrosunclassified